Probing jet base emission of M87* with the 2021 Event Horizon Telescope observations - Saurabh,; Müller, Hendrik; von Fellenberg, Sebastiano D.; Tiede, Paul; Janssen, Michael; Blackburn, Lindy; Broderick, Avery E.; Chavez, Erandi; Georgiev, Boris; Krichbaum, Thomas P.; Moriyama, Kotaro; Nair, Dhanya G.; et al. (EDP Sciences, 2026)
We investigate the presence and spatial characteristics of the jet base emission in M87* at 230 GHz, enabled by the significantly enhanced (u,v) coverage in the 2021 Event Horizon Telescope (EHT) observations. The integration of the 12-m Kitt Peak Telescope (USA) and NOEMA (France) stations into the array introduces two critical intermediate-length baselines to SMT (USA) and IRAM 30-m (Spain), providing sensitivity to emission structures at spatial scales of ~250 μas and ~2500 μas (~0.02 pc and ~0.02 pc). Without these new baselines, previous EHT observations of the source in 2017 and 2018 lacked the capability to constrain emission on large scales, where a "missing flux"of order ~1 Jy is expected to reside. To probe these scales, we analyzed closure phases-robust against station-based gain calibration errors-and model the jet base emission using a simple Gaussian component offset from the compact ring emission at spatial separations > 100 μas. Our analysis revealed a Gaussian feature centered at (ΔRA ~ 320 μas, ΔDec. ~ 60 μ as), projected separation of ~5500 AU, with an estimated flux density of only ~60 mJy, implying that most of the missing flux identified in previous EHT studies had to originate from different, larger scales. Brighter emission at the relevant spatial scales is firmly ruled out, and the data do not favor more complex models. This component aligns with the inferred position of the large-scale jet and is therefore physically consistent with the emission of the jet base. While our findings point to detectable jet base emission at 230 GHz, the limited coverage provided by only two intermediate baselines limits our ability to robustly reconstruct its morphology. Consequently, we treated the recovered Gaussian as an upper limit on the jet base flux density. Future EHT observations with expanded intermediate baseline coverage will be essential to constrain the structure and nature of this component with higher precision.